Bio-tar-derived porous carbon with high gas uptake capacities. (April 2021) - Tu, Ren; Sun, Yan; Wu, Yujian; Fan, Xudong; Wang, Jiamin; Cheng, Shuchao; Jia, Zhiwen; Jiang, Enchen; Xu, Xiwei
Abstract: The separation of CO2 from the nature gas is a challenge for solid sorbents. Bio-tar, a low cost and renewable carbon source, is employed to synthesis the ultra-microporous carbon materials. Carbonization of bio-tar with potassium hydroxide (KOH) at high temperatures (>700 °C) yields porous carbon materials with high surface areas of up to 2595 m 2 g −1 and high CO2 uptake performance of 5.35 mmol g −1 at 1 bar and 0 °C. This carbon material also shows good CO2 /CH4 selectivity in mixed gas and excellent cyclability. In gas breakthrough test, the retention time of bio-tar-derived carbon for carbon dioxide and methane adsorption is 849 s g −1 and 337 s g −1, respectively. The retention time of CO2 is 157 s g −1 at 150 °C while CH4 is nearly non-adsorption. The carbon material has good cycle performance for carbon dioxide adsorption. Molecular simulations suggest that CO2 density in micro and narrow mesopores will be increased at high pressures. This is consistent with the observation that these pores are mainly responsible for the material's high-pressure CO2 capacity. This study provides insights in designing of bio-tar material and further developing for CO2 capture from natural gas. Graphical abstract: CO2 emissions will have a significant impact on the environment and climate. In particular, natural gas as a clean energy source has broad application. But CO2 with a content of 2%-10% in natural gas will cause a large amount of CO2 emissions when applied, and reduce the quality of natural gas. Therefore, it is extremely important to develop inexpensive CO2 capture agents. In this study, bio-tar, a hazardous waste, is employed to prepare self-doped nitrogen porous carbon materials with ultra-high specific surface area, showing excellent CO2 capture performance and the ability to separate CO2 from CH4. Under high temperature conditions, it still retains a strong adsorption capacity for carbon dioxide. The DFT calculation shows that the material exhibits the best adsorption performance when the specific surface area is 2600 m 2 /g, which provides a guiding role in the synthesis of the bio-tar-derived carbon material. Image 1 Highlights: Synthesis of self-doped nitrogen porous carbon material using bio-tar as material. The maximum value of CO2 -adsorption is 5.35 mmol/g at 273 K. Gas breakthrough tests is employed to study the capture ability for separating CO2 . Good thermal stability enables recycling of the porous carbon sorbent.